Exploring green investment interest in Islamic finance: The case of Indonesian Green Sukuk among university students - Sukmaningrum, Lutfiah; Saputra, Rizal; Ariyanto, Muhammad Helmi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The escalating frequency of natural disasters in Indonesia, particularly hydrometeorological hazards, underscores the urgency of sustainable financing instruments that integrate environmental responsibility with Islamic ethical principles. The Indonesian Green Sukuk (IGS) represents such an instrument, yet little is known about the factors influencing young investors’ interest in it. Building on the Theory of Consumption Value (TCV), which comprises functional, social, religious, emotional, and knowledge dimensions, this study examines how these values shape students’ green investment interest. Methods: A quantitative correlational design was employed using cross-sectional data collected from 178 Universitas Gadjah Mada (UGM) students through an online questionnaire with a five-point Likert scale. Data were analyzed using ordinal logistic regression to test the influence of value dimensions, complemented by cluster tests to identify demographic variations. Findings: The results show that among the five TCV dimensions, only knowledge value significantly affects investment interest (odds ratio = 3.22, p < 0.05). Functional, social, religious, and emotional values were not significant. Cluster tests further reveal variations in investment interest based on gender, faculty affiliation, and income level, suggesting that demographic factors also play a role. Conclusion: Investment interest in IGS is primarily driven by cognitive understanding of its mechanisms, benefits, and sustainability impacts, rather than by functional, social, religious, or emotional considerations. Enhancing financial literacy is therefore essential to increase students’ engagement with sustainable Islamic financial instruments. Novelty/Originality of this article: This study contributes to the literature by applying TCV in the context of Islamic green finance among university students, a demographic often overlooked in prior research. It introduces the Integrated Greenvestment Class as an innovative literacy program to foster a generation of young investors who are financially literate, sustainability-oriented, and guided by Islamic ethical values in their financial decision-making.